Differential effects of opiate peptides and alkaloids on anterior pituitary hormone secretion. - Delitala, G; Grossman, A; Besser, M (1983)
In order to investigate the opiate receptors involved in the control of anterior pituitary hormone secretion, five different opioid drugs were administered intravenously to groups of 6 normal male subjects. Morphine (10 mg), methadone (10 mg), pentazocine (30 mg), nalorphine (10 mg) and 0.25 mg of the met-enkephalin analogue, DAMME, all caused similar increases in circulating prolactin with falls in serum LH and cortisol. Methadone and DAMME also elevated GH and TSH; morphine elevated TSH but not GH, nalorphine GH but not TSH. After pentazocine neither GH nor TSH changed. FSH failed to change significantly after any drug. All these changes, except serum cortisol, were antagonised by 4 mg naloxone. Taking into account the known receptor subtypes preferentially activated by each opiate, it is suggested that prolactin secretion is modulated by epsilon-receptors and TSH by mu-receptors. The control of ACTH probably involves delta-or kappa-receptors, that for LH kappa-or epsilon-receptors. It is not possible on present data to allocate a specific receptor mediating the opioid control of GH.